Nanofluid Assistance in Machining Processes- Properties, Mechanisms and Applications: a Review - Wit Grzesik (Journal of Machine Engineering)
A special group of hybrid assisted processes termed media-assisted processes which apply liquid media with special additives in the form of nanoparticles supplied to the cutting zone is overviewed. Special attention is paid to minimum quantity lubrication (MQL) technique with the use of nanofluids. In this review paper some important thermal and tribological effects resulting from the applications of various nanoparticles are outlined and compared. The MQL-nano cutting fluid mechanisms (rolling and ploughing) are described. In particular, some important quantitative effects concerning thermal and tribological behavior of the cutting process as well as surface quality are presented.